New Strategies and Practices of Design Education Under the Background of Artificial Intelligence Technology: Online Animation Design Studio - Tang, Tianran; Li, Pengfei; Tang, Qiheng (Frontiers in Psychology, 2022)
This study is based on the background of how artificial intelligence (AI) technology is applied to the field of creativity and design education to improve the design vision, teaching methods, and actual design productivity of practitioners. The purpose of the research is to compare traditional design education and new design education methods combined with AI technology. Taking the Technological Pedagogical Content Knowledge (TPACK) technology integration model as the starting point, a comprehensive evaluation is selected for different types of research to explore the animation design professional courses in design education, the content of students’ perception preferences, and the evaluation of ease of learning so as to conduct research and analyze AI technology. Design new education strategies and practice methods under the background. In the research, a comparative experimental study was conducted on 40 first-year students majoring in animation design. The results show that through online design studio project practice, with personalized project learning guidance, the learning needs of students to show a better trend, and customized learning and project practice content can enhance the learning experience and performance of students. In the future, we can further expand the scope of analysis, include more case studies, and conduct more comprehensive research, including how to deal with the expansion of the platform for students’ learning of design in situations similar to coronavirus disease 2019 (COVID-19) that profoundly affects our lives, and how the project is applied in practice.